Dayasaing Komoditas Bawang Merah di Kabupaten Majalengka, Jawa Barat - Rahmadona, Lola; Fariyanti, Anna; ,, Burhanuddin (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2017)
ABSTRACTShallot is included in the category of high value commodities, so that many farmers cultivate it. Indonesia still remains as net importer of shallot. The objectives of this study were to analyze the competitiveness of shallot farming in the district of Majalengka. Respondents were 37 farmers selected by using purposive sampling technique. The data were analyzed by the method of the Policy Analysis Matrix (PAM) to determine the level of profit and competitiveness. The result showed that shallot farming in the district of Majalengka was financially profitable, but economically unprofitable. The analysis of the competitiveness in the district of Majalengka showed the shallot farming have no competitiveness.Keywords: competitiveness, Policy Analysis Matrix, shallot farming ABSTRAKBawang merah termasuk dalam kategori komoditas bernilai tinggi, sehingga banyak petani yang mengusahakannya. Namun demikian Indonesia masih tetap sebagai net importir bawang merah. Tujuan dari penelitian ini ialah untuk menganalisis dayasaing komoditas bawang merah di Kabupaten Majalengka. Responden 37 petani yang dipilih dengan menggunakan teknik purposive sampling. Data dianalisis dengan menggunakan metode Policy Analysis Matrix (PAM). Hasil penelitian menunjukkan bahwa komoditas bawang merah di Kabupaten Majalengka menguntungkan secara finansial tetapi secara ekonomi tidak menguntungkan. Analisis dayasaing di Kabupaten Majalengka menunjukkan komoditas bawang merah tidak memiliki dayasaing.Kata kunci: dayasaing, Policy Analysis Matrix, usahatani bawang merah